The Spillover of Capital Inflows and The Role of United States Quantitative Easing on Thailand, Brazil, and India Countries’ Macroeconomic - Meepornsawan, Sarawut; Tansuchat, Roengchai (Asian Journal of Applied Economics, 2016)
In 2008, United States (U.S), their Conventional Monetary Policy can’t recover their economy. Thus, The Federal Reserve Bank must come out the use of Unconventional Monetary Policy known as “Quantitative Easing” (QE). But, the U.S. economy stills no sign of recovery and continues to employ this policy further. As a result, these lead the capital inflows to the Emerging Market Economies (EMEs) which have a good economic growth and higher yield in investment. Thus, this research aims to study the effect of capital inflows on macroeconomic variables of emerging economies comprising Thailand, Brazil, and India. The scope of this study is cover an announced of QE since the end of 2008 to 2013 and employ an approach of Markov-switching Vector Autoregressive model as a tool innovation to study the impact arising. The findings reveal that the changes in the growth rate of capital inflows in portfolio and direct investment in both expansion regime (Regime 1) and the recession regime (Regime 2) affect to the direction of the growth rate of the capital market group, interest rate group, exchange rate group, international trade group, the production group and the price index group in different directions, which was described by the results of the Intercept term that is regime dependent. In the case of the relationship between endogenous and exogenous variables, there are explained by autoregressive parameters term which is regime independent. Additionally, the response of the growth rate of the variables to the shock in the growth of the FPI and FDI tends to move in the steady state within 6 months. However, there were some variables moves in steady state in long period of time.